Underreaction, Overreaction, and Increasing Misreaction to Information in the Options Market - Poteshman, Allen M. (Journal of Finance, 2001)
This paper investigates options market reaction to changes in the instantaneous variance of the underlying asset. There are three main findings. First, options market investors underreact to individual daily changes in instantaneous variance. Second, these same investors overreact to periods of mostly increasing or mostly decreasing daily changes in instantaneous variance. Third, they tend to underreact (overreact) to current daily changes in instantaneous variance that are preceded mostly by daily changes of the opposite (same) sign. The third finding can reconcile the first two and is also consistent with well‐established cognitive biases.